The relationship between mathematical anxiety and learning motivation on mathematics learning outcomes of seventh-grade students in Tamansiswa environment - Elisabeth Ina Wee Logho; Istiqomah Istiqomah; Betty Kusumaningrum; Luc Bergman (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study investigates the relationship between mathematical anxiety, learning motivation, and mathematics learning outcomes among seventh-grade students in the Tamansiswa environment. Employing a quantitative ex-post facto method, data were collected from 56 students across two schools using questionnaires and academic performance records. The results revealed a significant and negative correlation between mathematical anxiety and learning outcomes, highlighting the detrimental effects of heightened anxiety on students' academic performance. Conversely, learning motivation demonstrated a significant positive influence, emphasizing its crucial role in fostering engagement and persistence in mathematics learning. The combined analysis of these variables showed that 52.2% of the variance in mathematics learning outcomes could be explained by the interaction between anxiety and motivation. Interestingly, despite high levels of anxiety, some students achieved strong learning outcomes, suggesting the presence of mitigating factors such as resilience or effective coping strategies. These findings underscore the importance of reducing anxiety and enhancing motivation through targeted educational interventions, such as supportive teaching practices and motivational strategies, to optimize mathematics learning outcomes. In conclusion, mathematics learning outcomes are shaped by a complex interaction between emotional and motivational factors. Reducing mathematical anxiety while simultaneously strengthening learning motivation is crucial for optimizing students’ achievement in mathematics. The study contributes empirically by providing evidence of the combined influence of anxiety and motivation within the Tamansiswa context, and practically by offering insights for educators to design instructional strategies that are both emotionally supportive and motivationally engaging. These findings reinforce the importance of integrating psychological considerations into mathematics instruction to promote more effective and inclusive learning environments.